Crowdfunding for Small Business Expansion : Evaluating the Impact of Community Participation in Resource Mobilization - Ruri Nurul Aeni Wulandari; Waspodo Tjipto Subroto; Norida Canda Sakti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Crowdfunding has emerged as an innovative method to support small business expansion, providing an alternative for entrepreneurs to access financial resources. This study aims to evaluate the impact of community participation in resource mobilization through crowdfunding. By analyzing data from various successful crowdfunding campaigns, the study identified the factors that influence the success of fundraising and how community engagement contributes to those outcomes. The findings show that community participation not only increases project trust and credibility, but also creates important emotional and social support for entrepreneurs. In addition, crowdfunding serves as an educational platform that increases public awareness of social and economic issues. This research provides insights for entrepreneurs and policymakers on the importance of community involvement in crowdfunding strategies, as well as broader implications for economic development. Through the evaluation of the impact of community participation, this study highlights the potential of crowdfunding as an effective tool for resource mobilization in the context of small businesses.